THE VOLUNTEER FACTOR IN THE DEPLOYMENT OF THE NATIONAL RESISTANCE MOVEMENT IN THE 1940S AND IN THE RESISTANCE TO THE FULLL-SCALE RUSSIAN INVASION: A COMPARATIVE ASPECT (Південний архів (історичні науки), 2025)
The purpose of the material is to compare and analyze the voluntary principles of joining the armed struggle for the acquisition (1940s) and preservation (2022, 2023) of national statehood. The methods of research within the framework of the specified topic were historical and logical, as well as problem-chronological, comparative-historical and prosopographic analysis. As a result of the study, one of the leading trends in staffing tactical units of the military-school structure, which emerged from the initiative of the “revolutionary” wing of the Organization of Ukrainian Nationalists in Galicia in the summer of 1943 ‒ the Ukrainian People’s Self-Defense, is outlined. This concerns the involvement of volunteers from the nationalist movement in the region (the territory of modern Ivano- Frankivsk region is primarily taken into account). The prerequisites and reasons for such a choice of the majority of the mentioned social stratum are emphasized. The emphasis is on the components of the ideological nature in the process of implementing the corresponding position. The defining component of the set of ideological prerequisites is presented. At the same time, relying on documents of the era and the testimonies of contemporaries, the comparison of its essence with the general guidelines and goals of the activities of both the radical wing of the domestic nationalist movement and the national interests of that time is emphasized. A general comparison of the latter with the events of the resistance to Russian aggression in the present is made. The personalistic dimension of the matter of staffing tactical units of the Ukrainian People’s Self-Defense is generally outlined. An attempt is made to conduct a general analysis of the life path, value orientations and ideals of individuals who joined the direct resistance to the invading forces on the basis of voluntary consent in February-March 2022.At the same time, the organizational affiliation of the mentioned personalities is taken into account. These are representatives of the National Scout Organization “Plast”. This, in turn, made it possible to carry out an attempt at a general analysis of the ideological basis of the aforementioned position of the participants of the Resistance movement during the Second World War and the modern Russian-Ukrainian wars. The conclusions of the study are to state similar trends in the process of establishing the state aspirations of the national community during the 40-s of the 20-th century and the 20-s of the 21-st century; the importance of the ideological component of the volunteer movement and the significance of the proper activities of public organizations of a national-patriotic nature in ensuring the implementation of the key principles of national statehood were noted.
Keywords: volunteers, ideology, Resistance movement, Organization of Ukrainian Nationalists, Ukrainian People’s Self-Defense, Ukrainian Independent United State, National Scout Organization of Ukraine «Plast», Armed Forces of Ukraine